Effects of glucose oxidase and organic acids on the properties of a model low sodium dough prepared from Harvest and Pembina CWRS wheat. (September 2019) - Hopkins, Erin J.; Hucl, Pierre; Scanlon, Martin G.; Nickerson, Michael T.
Abstract: This research investigates the impact of glucose oxidase (GO) addition in the presence of organic acids (acetic, ascorbic, citric, fumaric, lactic, or succinic) on several parameters of a reduced salt dough system (1.0% NaCl). These parameters include dough rheology, stickiness, freezable water content (FWC), and percentage of glutenin macropolymer (%GMP). Two cultivars were used: Harvest and Pembina which are known for their weak and strong dough characteristics, respectively. It was found that the inclusion of most of the acids at 1.2 mmol/100 g flour increased stickiness and reduced dough strength, but had no effects on %GMP and little increase in FWC. As expected, ascorbic acid defied the trends for rheology and stickiness since it has use as a dough strengthening agent; however, no synergistic effects were observed between it and GO. The inclusion of GO (0.001%/flour wt.) was able to mitigate some of the effects on rheology and stickiness, but GO had no effect on the freezable water content and %GMP. The mechanism of the interactions of these acids within the dough remains to be elucidated and GO still appears to have potential as a low sodium bread improver, but it requires testing in complete dough systems and final bread products. Highlights: Acid inclusion weakens doughs and increases stickiness. Glucose oxidase improves doughs both with and without acids. Ascorbic acid defies acid trends and improves doughs but not with glucose oxidase. Acid inclusion has few effects on glutenin macropolymer and freezable water content. Flour cultivar is important in all assessed parameters.